PENGARUH KEPERCAYAAN DAN KOMUNIKASI TERHADAP LOYALITAS PELANGGAN PADA PT SPECTRUM LINTAS SERVICE DI KOTA BATAM - Jurnal Ilmiah Manajemen Universitas Putera Batam (Universitas Putera Batam, 2018)
This Research aims to determine empirically the direct effect and simultaneous effect of variables trust, communication and customer loyalty. This research involved 83 customer of the PT Spectrum Lintas Service Batam as research sample. Based on the research results of reliability and validity testing showed that all the statements in each variable reliable and valid. Data were analyzed by using multiple regression analysis with statistical software, SPSS 20. The results of this research are : confidence positive and significant impact on customer loyalty, communication positive and significant impact on customer loyalty and trust and communication together positive and significant impact on customer loyalty.The trust have positive impact and significant on the customer loyalty with coefficient of 0,371. The communication have positive impact and significant on the customer loyalty with coefficient of 0,221. The trust and communication have positive impact and significant of the customer loyalty with coefficient of 1,597.